The Assimilation of Islamic Culture into Local Beliefs in The Sangihe Islands - Yusuf, Nasruddin; Yasin, Yasin; Mash'ud, Imam; Ilahude, Ridwan (Aqlam: Journal of Islam and Plurality, 2024)
Abstract: This study aims to analyze the process of cultural assimilation occurring between Islamic teachings and the local belief system of Masade in the Sangihe archipelago. Utilizing a qualitative approach, the research explores how the interaction between these two religious traditions results in changes in the practices and cultural identity of the local community. The findings indicate that although the adherents of Masade are divided into three groups (Hadun, Hamadun, and Mangkung) with differing practices, they maintain harmonious relationships and mutual respect, creating a new culture that emerges from the integration of elements from both belief systems. This research highlights the importance of tolerance and adaptation in the assimilation process, as well as its impact on social diversity within the community, contributing to the understanding of the dynamics of intercultural interactions..Key Words: Intercultural Interaction, Identity Formation, Social DiversityAbstrak: Penelitian ini bertujuan untuk menganalisis proses asimilasi budaya yang terjadi antara ajaran Islam dan kepercayaan lokal Masade di kepulauan Sangihe. Dengan menggunakan pendekatan kualitatif, penelitian ini mengeksplorasi bagaimana interaksi antara dua tradisi keagamaan ini menghasilkan perubahan dalam praktik dan identitas budaya masyarakat setempat. Hasil penelitian menunjukkan bahwa meskipun penganut Masade terbagi dalam tiga golongan (Hadun, Hamadun, dan Mangkung) dengan praktik yang berbeda, mereka tetap menjaga hubungan harmonis dan saling menghormati, menciptakan budaya baru yang merupakan hasil dari penggabungan elemen-elemen dari masing-masing kebudayaan. Penelitian ini menyoroti pentingnya toleransi dan adaptasi dalam proses asimilasi, serta dampaknya terhadap keberagaman sosial di masyarakat, memberikan kontribusi pada pemahaman tentang dinamika interaksi antarbudaya.Kata Kunci : Interaksi Antarbudaya, Pembentukan Identitas, Keberagaman Sosial